Academic motivation scale - reliability and validity evidence among undergraduate nursing students - Geisa Colebrusco de Souza; Everson Meireles; Vera Lúcia Mira; Maria Madalena Januário Leite (Universidade de São Paulo, 2021)
Objective: to assess the evidence of validity and reliability of the academic motivation scale (AMS) based on the internal structure. Method: this is a methodological study with 205 undergraduate nursing students. Dimensionality/internal structure of the AMS was assessed using factor analysis in the context of exploratory structural equation modeling (ESEM) and reliability of the factors was assessed by Cronbach's alpha (α) coefficient and composite reliability (CR) coefficient. Results: acceptable fit indexes were obtained (CFI = 0.92; RMSEA = 0.07; SRMR = 0.06) for a three-dimensional model: intrinsic motivation (10 items; α = 0.84; CR = 0.86); extrinsic motivation (8 items; α = 0.84; CR = 0.90); and demotivation (4 items; α = 0.84; CR = 0.88). A significant correlational pattern was found for the motivation continuum. Conclusion: the dimensionality analysis for the AMS presented a model with three factors: intrinsic motivation, extrinsic motivation and demotivation, and was considered a reduced alternative to the original version of seven factors. This study helped assess the validity of the measurement instrument and its theory refinement; further studies should be conducted to assess its invariance property.